Impact of the 2017 Blood Pressure Guidelines by the American Academy of Pediatrics in overweight/obese youth. Issue 4 (April 2019) - Di Bonito, Procolo; Valerio, Giuliana; Pacifico, Lucia; Chiesa, Claudio; Invitti, Cecilia; Morandi, Anita; Licenziati, Maria Rosaria; Manco, Melania; Giudice, Emanuele Miraglia del; Baroni, Marco Giorgio; Loche, Sandro; Tornese, Gianluca; et al.
Abstract : Objectives: The aim of this study was to compare the impact of the European Society of Hypertension Guidelines 2016 (ESHG2016 ) and the American Academy of Pediatrics Guidelines 2017 (AAPG2017 ) on the screening of hypertension and classification of abnormal left ventricular geometry (ALVG) in overweight/obese youth. Methods: This study included 6137 overweight/obese youth; 437 had echocardiographic assessment. Hypertension was defined using either ESHG2016 or AAPG2017 . ALVG was defined using 95th percentile for age and sex of left ventricular mass index (LVMi) and/or relative wall thickness (RWT) more than 0.38 (juvenile cut-offs) according to ESHG2016 or LVMi more than 51 g/h 2.7 and/or RWT more than 0.42 (adult cut-offs) according to AAPG2017 . Results: Prevalence of youth at a high risk of hypertension was 13% higher using AAPG2017 than ESHG2016 . The increase was larger in overweight youth at least 13 years of age (+43%). Using the juvenile cut-offs for ALVG, youth at a high risk of hypertension by ESHG2016 had an odds ratio [95% confidence interval (95% CI)] of 3.03 (1.31–7.05) for left ventricular concentric remodelling (LVcr) and 2.53 (1.43–4.47) for concentric left ventricular hypertrophy (cLVH) as compared with youth with normal LVG. Similarly, in youth at a high risk of hypertension by AAPG2017, the odds ratio for LVcr was 3.28 (1.45–7.41, P < 0.001) and 3.02 (95% CI: 1.73–5.27, P < 0.001) for cLVH. Using the adult cut-offs, no significant difference in ALVG was found with both guidelines. Conclusion: The prevalence of overweight/obese youth at a high risk of hypertension increased by 13% comparing AAPG2017 vs. ESHG2016. The juvenile cut-offs for ALVG were more effective than the adult criteria in intercepting individuals with a potentially higher cardiovascular risk.